Physical activity and depressive symptoms among community-dwelling older adults in the COVID-19 pandemic era: A three-wave cross-lagged study. (15th February 2022) - Li, Yuan; Su, Shaoyu; Luo, Biru; Wang, Jing; Liao, Shujuan
Abstract: The aim of the study is to determine the trajectories of physical activity and depressive symptoms and their reciprocal relationship among community-dwelling older adults in the COVID-19 pandemic era. The study population consisted of a cohort of 511 participants aged 60 years and over, who were recruited from eight community health centers in Ya'an, China. The Physical Activity Scale for the Elderly and the Patient Health Questionnaire were respectively used to measure physical activity and depressive symptoms at three time points: before the COVID-19 outbreak (T0 ), during the outbreak period (T1 ), and after the subsidence of COVID-19 (T2 ). The results revealed that physical activity and depressive symptoms fluctuated substantially across T0, T1, and T2 . In addition, more severe depressive symptoms at T0 and T1 were significantly associated with lower levels of physical activity at T1 and T2, but the obverse direction of physical activity being associated with subsequent depressive symptoms was not observed in the current study. These findings highlight the importance of supporting old people to remain physically active and combat mental distress early in a pandemic, and prevention and management of depressive symptoms may also be beneficial to promote physical activity.